Wypłaty pieniężne z zysku a płynność finansowa w przedsiębiorstwach agrobiznesu - Franc-Dąbrowska, Justyna (Cash Disbursements from Profit and Financial Liquidity in Agro-Industry Companies, 2007)
The research involved homogenous group of 15 joint-stock companies operating in farm and food industry listed on the Warsaw Stock Exchange in the years 2001-2004. The research hypothesis was positively confirmed: Return on equity in companies where decision was taken to disburse cash from profits was equal or higher then in companies where financial results were reinvested. The companies taking decisions to disburse cash from profit retained higher level of financial liquidity
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 163-173